2011
DOI: 10.1371/journal.pgen.1002054
|View full text |Cite
|
Sign up to set email alerts
|

A Latent Pro-Survival Function for the Mir-290-295 Cluster in Mouse Embryonic Stem Cells

Abstract: MicroRNAs (miRNAs) post-transcriptionally regulate the expression of thousands of distinct mRNAs. While some regulatory interactions help to maintain basal cellular functions, others are likely relevant in more specific settings, such as response to stress. Here we describe such a role for the mir-290-295 cluster, the dominant miRNA cluster in mouse embryonic stem cells (mESCs). Examination of a target list generated from bioinformatic prediction, as well as expression data following miRNA loss, revealed stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 43 publications
7
83
0
Order By: Relevance
“…Moreover, miR-290-295 cluster is reported to be highly enriched in the germ cell population of day 6 testis when compared to the somatic cell population . This cluster is a target of pluripotency factors, and in turn targets the pluripotency factors Oct3/4, Sox2 and Nanog (Zheng et al, 2011). It is shown that suppression of the miR-290 cluster, besides embryonic lethality, leads to the defective migration of PGC numbers in the gonads.…”
Section: Mir-371-3mentioning
confidence: 99%
“…Moreover, miR-290-295 cluster is reported to be highly enriched in the germ cell population of day 6 testis when compared to the somatic cell population . This cluster is a target of pluripotency factors, and in turn targets the pluripotency factors Oct3/4, Sox2 and Nanog (Zheng et al, 2011). It is shown that suppression of the miR-290 cluster, besides embryonic lethality, leads to the defective migration of PGC numbers in the gonads.…”
Section: Mir-371-3mentioning
confidence: 99%
“…[26][27][28] To check whether these miRs generally protect ESCs from apoptosis, we exposed ESCs transfected with anti-miRs to 5 Gy of X rays. In these conditions we observed increased apoptosis, as demonstrated by the accumulation of active caspase-3 ( Figure 4f).…”
mentioning
confidence: 99%
“…Thus, mouse-specific sequence variations in the 3′ UTRs of these genes gave rise to functional target sites. We additionally tested Caspase 2, a recently described miR-295 target with partially conserved target sites (28) and observed an 80% repression in response to transfection of miR-467a (Fig. 4D), indicating that these miRNAs can exert strong as well as moderate repression of targets.…”
Section: Target Sites Of Many Mouse-specific Sfmbt2 Cluster Mirnas Armentioning
confidence: 83%
“…While many of the identified target interactions are likely to be novel, a subset may functionally overlap with those of the miR-290-295 cluster which promotes proliferation (26) and survival (28). In some cases, single 3′ UTRs may be targeted by multiple cluster members, as was observed for Lats2 (a target of miR-467a and miR-466f-3p), a gene known to oppose proliferation and growth (32,34,35).…”
Section: Discussionmentioning
confidence: 99%